Continuous Renal Replacement Therapy for Pheochromocytoma Crisis With Multiple Organ Failure. (December 2015) - Seo, Masahiro; Yamada, Takahisa; Ozu, Kentaro; Fukunami, Masatake
Abstract : Abstract: Pheochromocytoma crisis is a feared and potentially lethal complication associated with excess release of catecholamine from the tumor, which might lead to multiple organ failure (MOF). The definitive treatment for pheochromocytoma is surgical resection. To safely proceed with surgery, hemodynamic stabilization in the acute phase is indispensable, but it might be extremely challenging in case of pheochromocytoma crisis with MOF even if the sufficient pharmacological drugs would be administered. Catecholamine is a dialyzable substance and is removed by renal replacement therapy. In this report, we described 2 cases of pheochromocytoma crisis with MOF, in which we succeeded in controlling acute unstable hemodynamics by means of catecholamine removal with continuous renal replacement therapy. These cases suggest that continuous renal replacement therapy may be effective to manage unstable hemodynamics because of massive catecholamine excretion in patients with pheochromocytoma crisis and MOF.